Kepuasan Menggunakan Search Engine bagi Mahasiswa (Studi Seach Engine Google) - Wismantoro Yohan (Semantik, 2011)
ABSTRACT: Web search engine is a part of non-transactional website Google is the biggest search engine that aims to manage useful information which is applicable to public, particulary university students. This research explores the positive attitude toward Google, a web search engine. The approach used is IT-Base Service Model. It encloses perceived benefit, ease-of-use. design quality, convenience, and sensation.keywords: Web, Search engine, Google, IT